Human rights and corruption - Rahman, Mizanur, 1956-; Empowerment Through Law of the Common People (Project) (Dhaka : Empowerment through Law of the Common People : Distributor, Palal Prokashoni, 2007)
Contributed articles; with reference to Bangladesh.
Includes bibliographical references.
Keywords: Corruption -- Bangladesh; Human rights -- Bangladesh